Progress in imaging the effects of psychosis susceptibility gene variants. (January 2013) - Redpath, Holly L; Lawrie, Stephen M; Sprooten, Emma; Whalley, Heather C; McIntosh, Andrew M; Hall, Jeremy
Genetic imaging has become an increasingly popular tool that utilizes neuroimaging techniques to investigate the impact of genetic variation on the structure, function and connectivity of the brain. Combining genetic and neuroimaging domains is a promising approach to further the understanding of the neural mechanisms involved in mediating the effect of genetic variants on psychosis risk, with the potential to explore individual vulnerability to psychiatric illness. Imaging genetics approaches have successfully been applied to a wide range of risk genes for schizophrenia. This article reviews the recent literature on genetic imaging in schizophrenia, using two key susceptibility genes for psychosis, DISC1 and NRG1, as examples. The authors explore challenges and future perspectives in the field, including the need for future research to focus on epistatic effects of multiple common variants, account for the complexity of gene–environment interactions, characterize rare high-risk structural variants and identify more effective neuroimaging paradigms that reach a higher threshold of heritability. Ultimately, this review highlights that genetic imaging remains a research technique, and further progress and integration with other techniques will be required before we can predict the onset and development of schizophrenia.